Antarctica's Gateways and Gatekeepers: Polar scenarios in a polarising Anthropocene. (December 2022) - Frame, Bob; Yermakova, Yelena; Flamm, Patrick; Nicklin, Germana; De Paula, Gabriel; Badhe, Renuka; Tuñez, Francisco
As the short to medium-term social and economic impacts of the COVID-19 pandemic dominate world issues, longer-term environmental and geopolitical concerns remain of great concern. However, the appetite for tackling complex transdisciplinary anthropogenic change processes may be receding rather than accelerating. In this essay, we propose that Antarctica, the continent of peace and science, a place that assumes a role as the global imaginary Other, where short- and long-term horizons co-exist, is a site where signs of global regeneration in the Anthropocene should be clear. To provoke discussion, we imagine two scenarios set in the five Gateway Cities of Antarctica to 2050. In the 'Gatekeepers' scenario, there is a fragmented global order with minimal unregulated behaviour based on narrowly defined national interests; in the 'Gateways' scenario, values-based partnerships generate novel institutional arrangements. By contrasting these polar opposites as a performative act, we highlight the need for future-making at the interface between science and policy.